2015
DOI: 10.1007/s10533-015-0127-y
|View full text |Cite
|
Sign up to set email alerts
|

Catchment biogeochemistry modifies long-term effects of acidic deposition on chemistry of mountain lakes

Abstract: Using relationships between the composition of precipitation and emission rates of sulphur and nitrogen compounds and dust from 1978 to 2012, we modelled concentrations of sulphate, nitrate, ammonium, chloride, and base cations and pH of precipitation in the Tatra Mountains (central Europe) back to 1900. The modelled precipitation chemistry exhibited a high degree of temporal coherence with the lake water chemistry in 1937 and during the period 1984-2014. The ionic composition of lake water reflected progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…, Kopácek et al. ,). Though there are other sources of P, DOM is the primary transporter of this nutrient to remote lakes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…, Kopácek et al. ,). Though there are other sources of P, DOM is the primary transporter of this nutrient to remote lakes.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have found that terrestrial mobility of P, driven by soil retention and size of the watershed, drives water concentration of TP and trophic status (Kopácˇek et al. , 2015 a , Kanˇa et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The steepest increase in Ca 2+ concentrations in Tatra Mountain lakes occurs in the same type of lakes that have increasing nutrient concentrations, including P (Kopáček et al 2015b;. These parallel trends in Ca and P concentrations suggest that elevated weathering rates due to climate change also could contribute to the increased P leaching in some alpine catchments.…”
Section: Introductionmentioning
confidence: 90%
“…Positive relationships between lake water DOC and TP concentrations (Kopáček et al 2015b; Fig. 4) may be associated with their linked export from soils.…”
Section: Nutrientsmentioning
confidence: 99%
“…Successful indices of change in lake sediment cores were developed. These took advantage of the sensitivity of diatom, chrysophyte, and some invertebrate species assemblages to lake pH, and synchronous changes in heavy metal concentrations that were indicative of industrial emission sources and biogeochemical/biological responses (Charles et al, 1989;Cumming et al, 1992;Evans et al, 2001;Kopáček et al, 2015a). Since 1980 and with the advent of controls on industrial emissions and socio-economic changes in industrial and agricultural production, there has been some recovery from acidification in certain lakes.…”
Section: Insights From Paleolimnology On the Effects Of Atmospheric Dmentioning
confidence: 99%